Tradisi Manganan - Novitasari, Nurul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study departs from the increasing urgency of strengthening religious moderation in multicultural Indonesian society. Local wisdom is considered one of the most contextual and effective approaches to grounding moderation values at the grassroots level. The purpose of this research is to describe the process of manganan implementation in Selogabus Village, Parengan District, Tuban Regency, and to analyze the religious moderation values embedded in this tradition. This research uses a qualitative ethnographic method, with data obtained through observation, in-depth interviews, and documentation involving village apparatus, Mbah Mudin as a religious-cultural leader, and local residents. The findings show that manganan is performed annually on Jumat Pahing after harvest season as an expression of gratitude to God and respect to ancestors. The tradition unites Muslim and non-Muslim residents through collaborative activities such as cleaning sacred places, praying together, and sharing meals. The study concludes that manganan functions not only as cultural heritage but also as a living medium of social practice that strengthens four indicators of religious moderation: national commitment, tolerance, anti-violence, and acceptance of local culture